2022
DOI: 10.1002/ctm2.771
|View full text |Cite
|
Sign up to set email alerts
|

GPR65 promotes intestinal mucosal Th1 and Th17 cell differentiation and gut inflammation through downregulating NUAK2

Abstract: G protein‐coupled receptor 65 (GPR65), a susceptibility gene for inflammatory bowel diseases (IBD), has been identified to promote Th17 cell pathogenicity and induce T cell apoptosis. However, the potential role of GPR65 in modulating CD4+ T cell immune responses in the pathogenesis of IBD stills not entirely understood. Here, we displayed that GPR65 expression was increased in inflamed intestinal mucosa of IBD patients and positively associated with disease activity. It was expressed in CD4+ T cells and robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…The elevated GPR65 + CD4 + cell findings in active IBD patients and pre‐clinical study outcomes reported by Lin et al. 5 support that GPR65 in CD4 + T cells acts as a positive regulator of IBD.…”
supporting
confidence: 66%
See 4 more Smart Citations
“…The elevated GPR65 + CD4 + cell findings in active IBD patients and pre‐clinical study outcomes reported by Lin et al. 5 support that GPR65 in CD4 + T cells acts as a positive regulator of IBD.…”
supporting
confidence: 66%
“…Lin and co‐authors 5 overexpressed GPR65 in cultured human CD4 + T cells to show that GPR65 prompts CD4 + T cells to polarize into T H 1 and T H 17 cells. Experimentally inducing colitis in conditional GPR65‐CD4 + T‐cell knockout mice resulted in a milder colitis phenotype compared to control mice.…”
mentioning
confidence: 99%
See 3 more Smart Citations